The density distribution function renewal process of three variables by means of the polynomial spline based on the b-splines - Prystavka Р. О. (Proceedings of National Aviation University (archive), 2003)
The question of asymptotic property research of local polynomial spline of three variables on the basis of the second order B-splines is considered in the article. Both the correspondent theorem and arguments as well as implications were formulated, proved and mentioned